Capital structure determinants: a literature review. (2015) - Pandey, Asheesh; Singh, Madan
In this paper, we present the literature review on determinants of capital structure of the research being done, both in India as well as internationally, in the last one and a half decade. We divide our study in two ways: one review for international research and second from Indian research. We further subdivide the research (both Indian as well as international) in two parts. In first part we review articles on determinants of capital structure being done at economy level and in the second part we provide literature review of papers on determinants of capital structure done at sector level. Finally, on the basis of our literature review, we provide a list of eleven common capital structure determinants found out of various studies.